2020
DOI: 10.3389/frvir.2020.582095
|View full text |Cite
|
Sign up to set email alerts
|

Visually Induced Motion Sickness on the Horizon

Abstract: Visually induced motion sickness is an unpleasant but common side-effect of many simulations and VR-applications. We investigated whether an earth-fixed reference frame provided in the simulation is able to reduce motion sickness. To do so, we created a moving starfield that did not contain any indicators of the spatial orientation of the observer. As the observer was simulated to move through the randomly oscillating starfield, a time-to-contact task had to be carried out. Two colored stars on collision cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Techniques to minimize cybersickness in the creation of virtual nature interventions also exist. When using a 360-degree camera, videos can be captured exclusively on a stationary tripod, as we have done here, or, when movement is desired, videos can be stabilized using an electronic handheld gimbal for moving video 58 with the horizon clearly visible 59 . Aside from cybersickness, HMDs can induce visual fatigue, also called eyestrain and describing the physiological strain or stress resulting from excessive demands on the visual system 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Techniques to minimize cybersickness in the creation of virtual nature interventions also exist. When using a 360-degree camera, videos can be captured exclusively on a stationary tripod, as we have done here, or, when movement is desired, videos can be stabilized using an electronic handheld gimbal for moving video 58 with the horizon clearly visible 59 . Aside from cybersickness, HMDs can induce visual fatigue, also called eyestrain and describing the physiological strain or stress resulting from excessive demands on the visual system 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, after viewing the single IAPS images, we immersed subjects in a simulation of a white starfield moving around them. The starfield simulation was adapted from previous work on VIMS by Hemmerich et al ( 2020 ) and included rotations. The parameters for the starfield simulation can be found in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…Rest frame hypothesis (RFH) predicts that in the absence of a visually stable cue such as the horizon (i.e., the point at which the sky and the Earth's surface appear to meet), MS becomes proportionally severe (Parker and Prothero, 2003). RFH is arguably related to the neural mismatch theory as it infers that a lack of cues for spatial orientation aggravates the visual-vestibular conflict (Hemmerich et al, 2020). However, when clear and reliable reference cues such as the horizon are present, MS can be far less severe as these provide relative spatial orientation cues to an observer.…”
Section: Motion Sickness Theoriesmentioning
confidence: 99%
“…A caveat of Moro et al (2017) is that the authors did not use a recognized measure of CS. Work by Kemeny et al (2017); Cao et al (2018); Hemmerich et al (2020); Whittinghill et al (2015) all found that the presence of RFs reduced symptoms of CS. Thus, CS is thought to be less severe in MR compared to VR because MR devices permit the user to perceive a physical reference cue (Lawson, 2005;Kuiper et al, 2019;Risi and Palmisano, 2019).…”
Section: Contributors To Csmentioning
confidence: 99%